(untitled) (Eurasian Research Bulletin, 2022)
This paper considers an automatic system for regulating the concentration of grape juice. The transition characteristic of the evaporation device was experimentally obtained, the dynamic characteristics of the control object were determined, the quality of regulation was assessed, and the stability of the closed ASR was determined